Teacher’s Strategies and Technique in Teaching Speaking - Nainggolan, Lasmaida; Manik, Sondang; Pasaribu, Arsen Nahum (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2025)
This study aims to investigate the role of Transformational Teachers in enhancing school climate and student well-being at SMP Negeri 1 Raya. The objectives are twofold: firstly, to examine the contribution of Transformational Teachers to school climate and student well-being, and secondly, to assess the impact of their practices on these factors. The qualitative methodology utilized in this research provides a comprehensive understanding of the intricate dynamics involved. Transformational Teachers, students, school administrators, and the school climate are the primary subjects of investigation. Through semi-structured interviews and direct observations, this study delves into the experiences, perceptions, and practices of these stakeholders. These findings highlight the Transformational Teachers at SMP Negeri 1 Raya play a pivotal role in cultivating a positive school climate and enhancing student well-being through multifaceted initiatives. Their dedication to innovative teaching methodologies, such as 'Student-Based Learning' and 'Differential Learning', fosters dynamic and inclusive learning environments that cater to individual student needs, thereby improving academic performance and enthusiasm for learning. Additionally, their proactive support for extracurricular activities and initiatives aimed at addressing issues like bullying and character building contribute to a safer and more supportive school environment. Furthermore, their collaborative leadership style promotes teamwork among staff, leading to a more positive work culture and efficient school administration. Ultimately, the impact of Transformational Teachers extends beyond academics to encompass holistic student development, ensuring that SMP Negeri 1 Raya maintains a vibrant and supportive climate conducive to students' overall well-being and success.